Applied Principles for Ensuring Economic Security of Economic Systems in the Conditions of Digitalization - Марусяк, Наталія; Марич, Максим (My University, 2021)
Within the article, a methodical approach to assessing economic security of regional economic systems in the context of digitalization, which is built using a systems approach, is proposed. The sequence of stages of the economic security assessment of regional economic systems in the conditions of digitalization is offered. To assess security of economic systems, it is justified to use the method of the hierarchical cluster analysis, which involves initial consideration of each of the objects as a separate cluster and then to combine them according to the similarity criterion until two final clusters are formed. The approbation of the offered methodical approach to the analysis of economic safety of economic systems in the conditions of active processes of digitization on an example of the regions of Ukraine is carried out.
Keywords: Economic security; Economic system; Region; Digitalization; System approach